The Rigidity Trap in Global Resilience: Neoliberalisation Through Principles, Standards, and Benchmarks - Rogers, Peter (Globalizations, 2013)
This article offers a critical social science perspective on the globalisation of disaster resilience. It is argued that the regulatory experimentation, typical of neoliberalisation, has begun to increase standardisation of emergency and security practices. Examples of this can be seen in the growth of general principles, non-statutory guidance, and international standards designed to improve resilience to disasters. This represents the creeping 'neoliberalisation' of 'disaster resilience'. When this results in over-standardisation a 'rigidity trap' is created. Regulatory experimentation may enhance the resiliency of organisations and infrastructure, but when standards and benchmarks seek to create 'resilient subjects' and 'resilient communities' the positive potential is lost in bureaucratic inflexibility. The neoliberalisation of resilience, if unchecked, will undermine the very flexible capabilities and adaptive capacity it is claimed that a focus on resilience can create. Este artículo ofrece una perspectiva de ciencia social crítica sobre la globalización de la resiliencia ante los desastres. Se sostiene que la experimentación reguladora, típica del neoliberalismo, ha comenzado a aumentar la estandarización de prácticas de emergencia y seguridad. Ejemplos de esto se pueden ver en el crecimiento de principios generales, orientaciones no reglamentarias y estándares internacionales, diseñados para mejorar la resiliencia a los desastres. Esto representa el crecimiento paulatino de la 'neoliberalización' de la 'resiliencia a los desastres'. Cuando esto resulta en un exceso de normalización, se crea una 'trampa de rigidez'. La experimentación normativa puede realzar la resiliencia de organizaciones e infraestructura, pero cuando los estándares y puntos de referencia buscan crear 'sujetos resilientes' y 'comunidades resilientes', el potencial positivo se pierde en la inflexibilidad burocrática. La neoliberalización de la resiliencia, sin verificación, entorpecerá las muy flexibles habilidades y la capacidad adaptiva que un enfoque en la resiliencia puede crear. 本文提出了关于灾难恢复方面的全球化的一个社会科学批评视角，认为调控性的试验，在新自由主义化的过程中的典型的调控性的实验已经开始增加紧急状态的标准化和安全惯例。这方面的例子可见于一般性的原则、非法规性的指针，以及专门用来改进灾后恢复的国际标准的增长。这代表着"灾难恢复"的缓慢"新自由主义化"。当着产生过分标准化时，"固化性陷阱"就产生了。调控性的实验可能增进组织机构和基础设施的恢复，但是，当标准和尺度试图创造"恢复性的主题"和"恢复性的共同体"，积极的潜力就在官僚的不灵活性中丧失。恢复的新自由主义化将削弱灵活性，适应性能力据说导致了对恢复的关注。 이 글은 재해 복원의 세계화에 대한 비판적 사회과학적 관점을 제시한다. 전형적인 신자유주의화인 규제 실험은 위기와 행동의 표준화를 높이기 시작햇다. 이러한 예들은 일반적인 원칙, 법으로 정하지 않은 지침과 국제적인 표준들의 증가에서 찾을 수 있다. 이것은 은밀하게 이루어진 '재해 복구'의 '신자유주의화' 를 보여준다. 이것이 과잉되게 표준화되었을 때, '경직성 덫'이 만들어진다. 규제적인 실험은 조직과 하부구조의 회복력을 높일 것이다. 그러나 표준과 기준이 '복구 주체'와 '복구 커뮤니티'를 만들고자 한다면, 긍정적인 잠재력이 관료적 경직성 속에서 사라진다. 저지되지 않는다면, 복구의 신자유주의화는 유연한 역량과 적응적 능력을 약화시킬 것이다. Эта статья предлагает критический взгляд социологии на глобализацию противодействия бедствиям. Утверждается, что регулирующее экспериментирование, типичное для неолиберализма, начало повышать уровень стандартизации аварийной и охранной практик. Примеры этого можно увидеть в росте общих принципов, неуставных руководств и международных стандартов, направленных на повышение устойчивости к бедствиям. Все это представляет собой медленно ползущий "неолиберализм" "противодействия бедствиям". Когда эти меры приводят к сверхстандартизации, "ловушку жесткости" можно считать созданной. Регулирующее экспериментирование может повысить устойчивость организации и инфраструктуры к бедствиям, но когда стандарты и критерии стремятся создать "устойчивые субъекты" и "устойчивые сообщества", положительный потенциал теряется в бюрократической негибкости. Неолиберализация противодействий бедствиям, если ее не остановить, будет подрывать возможности к гибкости и способности к адаптации.